METROPOLITAN GOVERNANCE AND MANAGEMENT: THE CASE OF GUADALAJARA METROPOLITAN AREA - Arias de la Mora , Roberto (Journal of Public Governance and Policy: Latin American Review, 2015)
This article aims to reflect about the analytical usefulness of the theoreticalconcept of the governance to understand recent trends oftransformation of societies settled in territories urbanistically consolidatedlarge, in order to assess their relevance front to the processes ofchange that are experiencing Latin American metropolis, the same asidentify their triggers factors, their strengths and limitations as well as itsopportunities and threats. For this purpose, the article focuses on thestudy of the recent experience of the institutional changes and publicmanagement deployed in the main metropolis of the West Central regionof Mexico: Guadalajara Metropolitan Area.The article is divided into three sections. The first one is dedicatedto clarify the author’s position respect the various approximations andtheoretical approaches that have been produced under the notionof governance, from which the relevant public administration is emphasizedas a discipline and professional practice in any process ofchange and social condition in mode of governance.The second section the most significant learning are presented on thestudy of metropolitan policy coordination, which led to the formalizationof the Guadalajara Metropolitan Area. Finally, some reflections onthe main components, as institutional as technical, that have shapedhitherto the unfinished process of metropolitan governance in Guadalajaraare advanced.